Powtoon Animation Video: A Learning Media for the Sixth Graders - G. A. P. Suprianti (Universitas Hamzanwadi, 2020)
In this global era, everything changes into technology-based likewise teaching method. In teaching, technology can be used as teaching variation and this study was aimed to develop technology-based English language learning media for sixth grade elementary students by using Powtoon animation video. This study’s objectives was for developing the prototype product. This study used Design and Development (DD) method by three steps based on ADDIE model. The stages are analysis, design, develop. Since the steps used were only three, then the product was only in the form of prototype product. In order to develop the prototype product, Need analysis, designing the product based on the analysis, and then development were done. The product was quantitatively analyzed by using expert judgment. The result of the experts judgment showed that the prototype product was categorized as an excellent media after some revisions and suggestions from material and IT expert.